ANALISIS PERBANDINGAN TOTAL DISSOLVED SOLID (TDS) DI PERAIRAN UTARA KABUPATEN SAMPANG DAN PERAIRAN UTARA KABUPATEN PAMEKASAN MENGGUNAKAN DATA VIIRS - Yauri Yusuf Munsyi; Siti Zainab (LPPM Universitas Abdurrab, 2025)
Sampang Regency and Northern Pamekasan Regency are areas with extensive marine and coastal potential, in Sampang Regency the Ketapang, Sokobanah and Banyuates areas and in Pamekasan Regency the Batumarmar, Waru and Pasean areas with fisheries development moving very rapidly along with the level of fishing. water fertility. Based on this background, it is necessary to conduct research on the value and distribution of Total Dissolved Solid (TDS) which will be used to compare the distribution of sedimentation on the North coast of Sampang Regency and Pamekasan Regency using remote sensing satellite data technology focusing on 2019 - 2023. Measurements Total Dissolved Solid (TDS) is based on the dissolved solids that have been tested. Total Dissolved Solid (TDS) are dissolved solids that cause sea water turbidity. The linear algorithm equation model with the equation y = 7439.2x + 21.525 and R² value = 0.1847 with a correlation value of 0.880075 is a very low correlation value, and for Pamekasan Regency the highest The appropriate image data is at a wavelength of 671 nm. The linear algorithm equation model with the equation y = 18.434x + 34.476 and the R² value = 0.0335 with a correlation value of 0.596882 is a very low correlation value. From this research, it is hoped that it can provide information on the high and low levels of turbidity in a body of water which can prevent the entry of sunlight into the water as well as knowing the thematic map of the distribution of Total Dissolved Solids (TDS) so that it can be used as a guide in the construction of coastal buildings.